PENGARUH PERBEDAAN DURASI APLIKASI NON RINSE CONDITIONER TERHADAP PENETRASI KOMPOMER PADA DENTIN GIGI SULUNG Evaluasi Scanning Electron Microscopy - Tri Putriany Agustin; Ismu Suharsono Suwelo; Margaretha Suharsini (Faculty of Dentistry, Universitas Indonesia, 2015)
The purpose of this study was to determine the influence of application time of Non Rinse Conditioner (NRC) on Compomer (Dyract, Dentsply) penetration in dentin of primary teeth. The simple was 30 mandibular primary incisors divided into 3 groups by application time (10,20, and 30 seconds). The penetration of Compomer was measured from 30 teeth using SEM (2000x mag). One way ANOVA test showed significant differences between the three application times (F=10,7074,738, p=0,001), and Tukey test also indicated significant differences between the groups (p=0,001). Longer periods of NRC application increases the application of Compomer.